String theory and black hole physics: locality, effective field theory and chaos - Rojas - Fernandez; Francisco (2023)
RESULTS OBTAINED:For each specific goal, describe or summarize the results obtained. Relate each one towork already published and/or manuscripts submitted. In the Annex section includeadditional information deemed pertinent and relevant to the evaluation process.The maximum length for this section is 5 pages. (Arial or Verdana, fontsize 10).The main goals of this project were in realm of quantum gravitational aspects ofblack holes physics. Although the original motivations of this project were to workin string field theory and its connections with the chaotic properties of black holehorizons, these changed a bit during the course of the project leading to new linesof research that concluded with publications in these new topics. In the followingparagraphs we list these results.Each of these three sections below correspond a published article.Meron black hole and gravitational isospin effect[JHEP 1906 (2019) 081]In this work we were able to construct an analytic black hole solution of the Einstein-Yang-Mills theory in five dimensions in which the gauge field is of Meron-type: itis proportional to a pure gauge, and it has a non-trivial topological charge. Oursolution, referred to as ”meronic black hole”, has only one integration constant,namely, its mass. The thermodynamics of the meronic black hole is similar to thatof Reissner-N¨ordstrom. Here, however, the analog of the electric charge is the Yang-Mills coupling, which is not a thermodynamical variable, but a fundamental constant,and therefore its variation does not appear in the first law. In the case of a negativecosmological constant, there is a first-order phase transition when the cosmologicalscale is big compared to the one defined by the Yang-Mills coupling.We also report a novel and non-trivial effect: the present solution shows that thetotal angular momentum of the composite system of a spinless particle (with in-ternal isospin quantum numbers) and the Meron black hole showed here, presentshalf-integer eigenvalues, thus, describing a fermion. Such a ...